Prescription for complaints (London : Video Arts, 1975)
This film shows that complaints are an oppurtunity to do it right - a second chance from your costumer. It gives reasonable step by step points that focus on the needs of the complainer as well as solution of the complaint
Keywords: Complaints (Retail trade)